The relationships between reading mindsets, reading engagement, and reading comprehension performance in the Saudi EFL context - Muhammad Waleed Shehzad; Mehwish Zahoor; Sumaira Sarfraz; Shazma Razzaq (Indonesian Journal of Applied Linguistics, 2023)
This study determines the relationship between reading mindsets and reading comprehension performance with the use of reading engagement as a mediating variable. It drew on Dweckâ€™s (1999) mindset theory and employed a correlational research design to collect data from 567 EFL undergraduate students majoring in English in three public universities in Saudi Arabia. The data collection was conducted by distributing two questionnaires and administering a reading comprehension test. The collected data were analyzed using a two-phase structural equation modeling approach (i.e., measurement and structural models). The results indicated that there was a significant correlation between a growth reading mindset and reading engagement. Nevertheless, a significant yet negative correlation was revealed between a fixed reading mindset and reading engagement. Moreover, there was a significant and positive correlation between reading engagement and reading comprehension performance. Lastly, the findings showed that reading engagement served as a mediating variable in determining the correlation between reading mindsets and reading comprehension performance. The relevance of the current study stems from the dearth of research on reading mindsets. Also, previous studies have not focused on exploring the correlation between mindsets and performance in the EFL context. Therefore, the current study is expected to benefit EFL readers, instructors, and policymakers.Â  Â